The «Viva La Pepa» Crosses Borders: the Sons of the Constitution of Cadiz - Rodríguez López-Brea, Carlos M. (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
The Constitution of Cadiz was the most far reaching Spanish constitution. Following the triumph of the Spanish liberal revolution of 1820, its prestige increased and it became the first crack in the wall for the Vienna system of international relations. The Spanish example encouraged successive revolts in Two Sicilies, Portugal and Piedmont-Sardinia. In each of these examples, the Constitution of Cadiz played an essential role, to the extent that it was provisionally adopted in both Italian kingdoms. In Two Sicilies and Portugal, parliaments reformed the Spanish charter to suit the demands and requirements of the local revolutionaries. Whilst the Italians gave it a federal aspect, the Portuguese expanded upon the civil and political rights recognized in Spain. This article examines the details of these processes, which were possible only due to the flexibility and ambiguity of La Pepa, whose –most– revolutionary principles were mixed with other more traditional ones.
Keywords: Constitution of Cadiz; Dos Sicilias; Portugal; Piedmont-Sardinia; revolts of 1820-1821